Amyloidosis in cystic fibrosis. (August 2019) - Simpson, Thomas; Elston, Caroline; Macedo, Patricia; Perrin, Felicity
Abstract: As the life expectancy of patients with cystic fibrosis has increased, greater attention has been paid towards the diagnosis and management of the longer term consequences of the condition. A recognised but rare complication of the disease is the development of secondary amyloidosis. Whilst deposition of amyloid protein has been reported in a high proportion of patients with cystic fibrosis at post-mortem[1] and Serum Amyloid A protein has been shown to correlate with disease activity and response to antibiotics[2], the manifestation of clinical disease remains extremely uncommon. The prognosis for patients with amyloid secondary to cystic fibrosis in published reports has been historically bleak[3–6], however there may be novel approaches in the era of biological therapies. The theoretical potential for an increase in the incidence of secondary amyloid amongst the population of cystic fibrosis patients who are experiencing much longer lifespans means that it is worthwhile to consider the condition and its possible treatments in more detail. We report a case and a review of the literature.